Soluble Megalin is Reduced in Cerebrospinal Fluid Samples of Alzheimer’s Disease Patients - Spuch, Carlos; Antequera, Desireé; Pascual, Consuelo; Abilleira, Soledad; Blanco, María; Moreno-Carretero, María José; Romero-López, Jesús; Ishida, Tetsuya; Molina, Jose Antonio; Villarejo, Alberto; Bermejo-Pareja, Felix; Carro, Eva (Frontiers in Cellular Neuroscience, 2015)
Megalin or low-density lipoprotein receptor related protein-2 (LRP-2) is a member of the low-density lipoprotein (LDL) receptor family which has been linked to Alzheimer’s disease (AD) by clearing brain amyloid β-peptide (Aβ) across the blood-cerebrospinal fluid barrier at the choroid plexus. Here, we found a soluble form of megalin secreted from choroid plexus epithelial cells. Soluble megalin levels were also localized in the human cerebrospinal fluid (CSF), being reduced in AD patients. We have also shown that soluble megalin binding to Aβ is decreased in the CSF of AD patients, suggesting that decreased sequestration of Aβ in the CSF could be associated with defective clearance of A and an increase of brain Aβ levels. Thus, therapies which increase megalin expression at the choroid plexus and/or enhance circulating soluble megalin hold potential to control brain A-related pathologies in AD